Position paper of the expert panel of the Polish Society of Menopause and Andropause on the use of Oestrogel® in menopausal hormone therapy* - Bińkowska, Małgorzata; Paszkowski, Tomasz; Skrzypulec-Plinta, Violetta; Zgliczyński, Wojciech (Menopause Review/Przegląd Menopauzalny, 2025)
This position paper of the expert panel presents a comprehensive review of the efficacy, safety, and clinical application of bioidentical hormone replacement therapy (HRT), with particular focus on transdermal 17-oestradiol gel (Oestrogel ® ). Bioidentical hormones – chemically identical to endogenous human hormones – are increasingly recognised as the preferred option in modern HRT, consistent with current international guidelines. Based on a review of randomised clinical trials and observational studies (sourced primarily from PubMed and Medline), transdermal oestradiol demonstrates a superior safety profile compared to oral formulations. Benefits include stable serum oestradiol levels without supraphysiological fluctuations; minimal impact on hepatic synthesis of procoagulant factors, triglycerides, hormone-binding proteins (SHBG, TBG, CBG), and inflammatory mediators (e.g. C-reactive protein); no increased risk of venous thromboembolism or ischaemic stroke; and the ability to use lower doses while maintaining efficacy. Additional advantages are a more physiological E2/E1 ratio, reduced inter-individual variability, and the option to monitor serum oestradiol levels. Oestrogel ® supports dose flexibility and personalisation, allowing treatment to be tailored according to patient needs and guideline-based therapeutic schemes. When combined with micronised progesterone – the gold-standard progestogen for endometrial protection and the preferred option due to its favourable overall safety profile – this form of HRT offers a modern, well-tolerated, and individualised approach to the management of menopausal symptoms and osteoporosis prevention.